Upcycling celebrations : a use-what-you-have guide to decorating, gift-giving & entertaining - Seo, Danny (Running Press Book Publishers, 2012)
Presents many projects for creative "upcycling"--using used and recycled products to create extraordinary gifts and decorations for celebrations from New Years Eve through Christmas.